(3JfbjM GdebGUO GdCUhdjI aj TQM JdNjU GdahGFO GdMGFQjIs - (3GdbRhjfj, GdMGFQj, GdTjQGRj, eMeO MSf Hf eMeO eYUhe, J (B1240 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3EfG bO PcQfG aj cJGHfG cTa GdZWGA Yf hLhg eQGSe GdGgJOGA JaVjd GdYdhe GdeMehOI hGdePeheI hHjfGgG HhLhg hGVMI eYdheI dcWGaI GdWdGH eagheI hbSefG GdChdi Edi eG jNJU faYg (B...s
(3BNQgG (B:s
... (3GdPj CJi Hg eTOG faSg Ch GdJSdSd Ef cGf eTOg Xfj BNQ hgcPG eY Cfg eYGQV HeG JbOe aQLMGfg Ydjg jMJGL Edi eQLM bWYj hdjS eG jajO GdXf acja HGdbWYj hQGHYgG Gf Odjd GdfHhI (B...s
(3JHUQI GdYfhGf (B:s
(3Ydi WQJg (B: (3TQM edNU GdahGFO GdSfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\92s
(3GdPQjYI (B4\2967s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs